2021
DOI: 10.3389/fpubh.2021.694836
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Policymakers on the Introduction and Scale-Up of HIV Self-Testing and Implication for National HIV Programming in Ghana

Abstract: Background: HIV self-testing (HIVST) has the potential to greatly increase HIV testing uptake, particularly among key populations (KPs) at higher risk for HIV. Studies have shown high acceptability and feasibility of HIVST among various target populations globally. However, less is known about the perspectives of policymakers, who are critical to the success of HIVST implementation. Their views on barriers to the introduction and scale-up of self-testing are critical to understand in order for HIVST to become … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…The categories and sub-categories emerging from the transcripts were nalized into a codebook with clear de nitions. The codebook and database with transcripts were entered into a qualitative analysis software package (QSR NVivo 11) (15). Two trained qualitative research assistants coded the transcript.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The categories and sub-categories emerging from the transcripts were nalized into a codebook with clear de nitions. The codebook and database with transcripts were entered into a qualitative analysis software package (QSR NVivo 11) (15). Two trained qualitative research assistants coded the transcript.…”
Section: Discussionmentioning
confidence: 99%
“…While the acceptability of PrEP by end-users, especially high risk groups like MSM and FSW, is well documented, the views of policymakers and service providers has not been well researched (10)(11)(12)(13)(14). Understanding policy makers' awareness, attitudes, perceptions, and preferences around a health product such as PrEP is very important in guiding its introduction and roll-out (15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…actors. Except for a few papers in crisis management (Ahlqvist et al, 2020;Gabler et al, 2017) and sustainability (Giannakis and Papadopoulos, 2015), the policymakers' perspective remains under-studied (Ho et al, 2015;Nagai et al, 2021;Pournader et al, 2020). Only a few papers have addressed the role of policymakers in depth and/or shown that policymakers can also make a positive contribution to SCRM.…”
Section: Scrms In Normal and Abnormal Timesmentioning
confidence: 99%
“…Yaroson et al (2021) demonstrated how policymakers can play the role of intermediaries in coping with risk resulting from COVID-19 in pharmaceutical supply chains. Nagai et al (2021) took the policymaker's perspective in their study of HIV programming in Ghana. Tucker et al (2020) compared market-based interventions and regulatory changes and concluded that redundancy regulations would be at least as efficient as market-based solutions to the shortage problem.…”
Section: Scrms In Normal and Abnormal Timesmentioning
confidence: 99%